2020
DOI: 10.15252/emmm.202013424
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum level of sphingosine‐1‐phosphate: a novel predictor of clinical severity in COVID‐19

Abstract: The severity of coronavirus disease 2019 (COVID‐19) is a crucial problem in patient treatment and outcome. The aim of this study is to evaluate circulating level of sphingosine‐1‐phosphate (S1P) along with severity markers, in COVID‐19 patients. One hundred eleven COVID‐19 patients and forty‐seven healthy subjects were included. The severity of COVID‐19 was found significantly associated with anemia, lymphocytopenia, and significant increase of neutrophil‐to‐lymphocyte ratio, ferritin, fibrinogen, aminotransfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 37 publications
(50 reference statements)
8
78
1
Order By: Relevance
“…The contribution of cell-mediated immunity, both innate and acquired, is yet unclear, though lymphopenia appears to be one of the main features of this viral disease 37 , 38 and also the presence of an atypical monocyte population 39 . It has been also reported that increased levels of neutrophil‐to‐lymphocyte ratio (NLR) reflecting an enhanced systemic inflammation may predict the clinical severity and suggest a poor prognosis 40 , 41 .…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of cell-mediated immunity, both innate and acquired, is yet unclear, though lymphopenia appears to be one of the main features of this viral disease 37 , 38 and also the presence of an atypical monocyte population 39 . It has been also reported that increased levels of neutrophil‐to‐lymphocyte ratio (NLR) reflecting an enhanced systemic inflammation may predict the clinical severity and suggest a poor prognosis 40 , 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, S1P was exhibiting strong predictive value for admission to ICU and patient outcome, for morbidity and severity of the clinical course. As a consequence, restoration to normal S1P-values was supposed as a therapeutic strategy in patients with COVID-19 (96).…”
Section: Sphingolipidomic In Infection and Sepsismentioning
confidence: 99%
“…The article in this issue of EMBO Molecular Medicine by Marfia and colleagues (Marfia et al , 2021) asks such a simple and impertinent question. They suggest a potential mechanistic linkage between a serum measurement of sphingosine‐1‐phosphate (S1P) and the progression to and outcome of the serious inflammatory phase of COVID‐19 infection.…”
Section: Figure S1p/hdl As a Prognostic Indicator For Icu Entry And Mmentioning
confidence: 99%
“…In contrast, S1P1 receptor antagonists exacerbated cytokine storm and lethality (Teijaro et al , 2016). The role of S1P signaling tone is tantalizingly framed in the Marfia et al (2021) study.…”
Section: Figure S1p/hdl As a Prognostic Indicator For Icu Entry And Mmentioning
confidence: 99%
See 1 more Smart Citation